AN IMPLEMENTATION ETHNOMATHEMATICS (BAY TAT CAKES) TO IMPROVE CONCEPTUAL UNDERSTANDING - Nur Atikah (Jurnal Math-UMB.EDU, 2024)
This research is a quantitative study with the aim of utilizing the ethnomathematics of Bay Tat cakes to improve students' understanding of mathematical concepts. The subjects in this research were 24 students in the control class and 24 students in the experimental class. The instrument used in this research is a written test to see the extent to which students' understanding of concepts has developed. The analysis technique used is descriptive and inferential statistical analysis. The results of this study showed that there was a higher increase in the experimental class than in the control class. This can be seen from the N gain score in the control class of 0.24, the increase in students' conceptual understanding is in the weak category. Meanwhile, in the experimental class, the N gain score was 0.42, which shows that students' understanding of concepts has increased significantly. Based on inferential analysis, the calculated t value obtained was 2.23 > t table, namely 2.01, meaning that Ho was rejected or met the influence criteria and it was seen that there was an increase in students' conceptual understanding after applying Bay Tat cake ethnomathematics during mathematics learning. Keywords: ethnomathematics, bay tat cake, concept understanding, mathematics.